2018
DOI: 10.3390/ijms19020458
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pharmacology of Rosmarinic and Salvianolic Acids: Potential Seeds for Alzheimer’s and Vascular Dementia Drugs

Abstract: Both caffeic acid and 3,4-dihydroxyphenyllactic acid (danshensu) are synthesized through two distinct routs of the shikimic acid biosynthesis pathway. In many plants, especially the rosemary and sage family of Lamiaceae, these two compounds are joined through an ester linkage to form rosmarinic acid (RA). A further structural diversity of RA derivatives in some plants such as Salvia miltiorrhiza Bunge is a form of RA dimer, salvianolic acid-B (SA-B), that further give rise to diverse salvianolic acid derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 153 publications
(228 reference statements)
0
56
0
Order By: Relevance
“…According to the authors' data [38], lithospermic acid B makes up 1.0%-9.7% of polyphenol content. It was reported that this compound was an efficient free-radical scavenger that could be used to treat cardiovascular diseases and play a beneficial role in Alzheimer's treatment [49,50]. The presence of didehydrosalvianolic acid B in peppermint leaf was reported previously by Krzyzanowska and co-workers [36].…”
Section: Discussionmentioning
confidence: 62%
“…According to the authors' data [38], lithospermic acid B makes up 1.0%-9.7% of polyphenol content. It was reported that this compound was an efficient free-radical scavenger that could be used to treat cardiovascular diseases and play a beneficial role in Alzheimer's treatment [49,50]. The presence of didehydrosalvianolic acid B in peppermint leaf was reported previously by Krzyzanowska and co-workers [36].…”
Section: Discussionmentioning
confidence: 62%
“…In particular, salvianic acid A is considered a superior antioxidant and one of the main therapeutic components for cardiac dysfunctions [25,38]. Moreover, it was proposed that salvianolic acids, identified as the main bioactive compounds in Salvia spp., could possess pharmacological properties useful to counteract a wide range of human pathologies [37,39]. The presence of these compounds in basil could improve the nutraceutical and technological value of this crop for food and pharmaceutical industry.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, there are quite many other studies that show beneficial activities of plant derived natural products in alleviation of oxidative stress related cellular damage [37]. Among the compounds showing such properties, there are many polyphenols, such as resveratrol [12], anthocyanins [38], caffeic acid oligomers [39], and many other [37]. Hydroxylated xanthones have been also reported as able to protect against neuronal damage in various models.…”
Section: Discussionmentioning
confidence: 99%